2019
DOI: 10.1016/j.jhep.2018.12.038
|View full text |Cite|
|
Sign up to set email alerts
|

Non-nucleoside reverse transcriptase inhibitor efavirenz activates PXR to induce hypercholesterolemia and hepatic steatosis

Abstract: Background & Aims:The most prescribed non-nucleoside reverse transcriptase inhibitor efavirenz has been associated with elevated risk for dyslipidemia and hepatic steatosis in HIVinfected patients but the underlying mechanisms remain elusive. Here we investigated the role of pregnane X receptor (PXR) in mediating the adverse effects of efavirenz on lipid homeostasis.Methods: Cell-based reporter assays, primary cell culture, and multiple mouse models including conditional knockout and humanized mice were combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 30 publications
6
91
2
Order By: Relevance
“…PXR is expressed at high levels in both liver and intestine, which are essential for whole-body lipid homeostasis. To define the tissue-specific role of PXR in xenobiotic and lipid metabolism, we have recently successfully generated hepatocyte-specific PXR-deficient mice (termed as PXR ΔHep ) by crossing mice carrying PXR flox alleles (PXR fl/fl ) with Albumin-Cre transgenic mice (29). For the current study, PXR fl/fl mice were also crossed with Villin-Cre transgenic mice to generate intestinal epithelial cell-specific (IEC-specific) PXR-deficient mice (PXR ΔIEC ) (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.125657DS1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PXR is expressed at high levels in both liver and intestine, which are essential for whole-body lipid homeostasis. To define the tissue-specific role of PXR in xenobiotic and lipid metabolism, we have recently successfully generated hepatocyte-specific PXR-deficient mice (termed as PXR ΔHep ) by crossing mice carrying PXR flox alleles (PXR fl/fl ) with Albumin-Cre transgenic mice (29). For the current study, PXR fl/fl mice were also crossed with Villin-Cre transgenic mice to generate intestinal epithelial cell-specific (IEC-specific) PXR-deficient mice (PXR ΔIEC ) (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.125657DS1).…”
Section: Resultsmentioning
confidence: 99%
“…Animals. Mice carrying PXR flox alleles (PXR fl/fl ) on C57BL/6 background were generated by using mouse embryonic stem cell clones containing conditional PXR flox allele from International Knockout Mouse Consortium (EUMMCR, EPD0141_1_G04) (29). PXR fl/fl mice were further crossed with Villin-Cre (The Jackson Laboratory; catalog 004586) or Albumin-Cre transgenic mice (The Jackson Laboratory; catalog 003574) to generate PXR ΔIEC or PXR ΔHep .…”
Section: Methodsmentioning
confidence: 99%
“…However, its role in the regulation of cholesterol homeostasis is more controversial. The anti-HIV drug Efavirenz has been recently shown to induce steatosis and hypercholesterolemia, an effect that was absent in a model of hepatic deletion of PXR [12]. These perturbations were mediated through increased fatty acid transport and cholesterol synthesis, via the PXR-dependent regulation of Cd36 and Sqle .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which PXR activation induces perturbations of lipid metabolism are not fully elucidated. Recently, it was shown that the activation of intestinal PXR signaling induced dyslipidemia and intestinal cholesterol accumulation [11], while activation of hepatic PXR signaling was sufficient to promote hypercholesterolemia and hepatic lipid accumulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent preclinical model has shown a putative mechanism linking efavirenz to the development of steatosis through pregnane X receptor activation and the disruption of fatty acid transport and cholesterol biosynthesis. ( 24 )…”
Section: Link Among Nash Hiv and Artmentioning
confidence: 99%